2002
DOI: 10.1038/ng829
|View full text |Cite
|
Sign up to set email alerts
|

Increased insulin sensitivity despite lipodystrophy in Crebbp heterozygous mice

Abstract: The CBP protein (cAMP response element binding protein (CREB) binding protein) is a co-activator for several transcription factors with a wide range of important biological functions, such as sterol regulatory element binding proteins (SREBPs), CCAAT/enhancer-binding proteins (C/EBPs), nuclear receptors (including peroxisome proliferator-activated receptors, PPARs), and signal transducers and activators of transcription (STATs). In contrast to these individual transcription factors, the biological roles of CBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
89
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(98 citation statements)
references
References 29 publications
6
89
0
3
Order By: Relevance
“…Our study presents strong evidence that CBP and p300 have distinct functions in the regulation of survivin transcription. The results are consistent with recent publications suggesting nonredundant roles for CBP and p300 in cell growth, differentiation and development, in spite of their high degree of homology (Kawasaki et al, 1998;Yao et al, 1998;Kung et al, 2000;Yamauchi et al, 2002;Roth et al, 2003). Rebel et al (2002), using a hematopoietic stem cell (HSC) model, concluded that CBP but not p300 is essential for HSC self-renewal, whereas p300 is critical for proper hematopoietic differentiation.…”
Section: Discussionsupporting
confidence: 82%
“…Our study presents strong evidence that CBP and p300 have distinct functions in the regulation of survivin transcription. The results are consistent with recent publications suggesting nonredundant roles for CBP and p300 in cell growth, differentiation and development, in spite of their high degree of homology (Kawasaki et al, 1998;Yao et al, 1998;Kung et al, 2000;Yamauchi et al, 2002;Roth et al, 2003). Rebel et al (2002), using a hematopoietic stem cell (HSC) model, concluded that CBP but not p300 is essential for HSC self-renewal, whereas p300 is critical for proper hematopoietic differentiation.…”
Section: Discussionsupporting
confidence: 82%
“…We recently demonstrated that CBP and p300 have distinct functions in the regulation of TCF͞␤-catenin-mediated survivin transcription (53). The results are consistent with recent publications suggesting nonredundant roles for CBP and p300 in cell growth, differentiation, and development, despite their high degree of homology (54)(55)(56)(57)(58). Rebel et al (59), using a hematopoietic stem cell (HSC) model, concluded that CBP (and not p300) is essential for HSC self-renewal, whereas p300 is critical for proper hematopoietic differentiation.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, mice with a heterozygous deficiency in the coregulator CREB-binding protein (CBP) are lipodystrophic, and they are protected from diet-induced obesity (29). The phenotypic similarities between the SRC-3 Ϫ/Ϫ and CBP ϩ/Ϫ mice could in part be explained by the established fact that SRC-3 and CBP usually act in concert to regulate gene expression.…”
Section: Discussionmentioning
confidence: 99%